The degradation products of aniline in the solutions with ozone and kinetic investigations - Turhan, Kadir; Uzman, Suheyla (WILEY-V C H VERLAG GMBH, 2007)
Aromatic compounds are extensively used in several industries and can cause pollution in water sources. This work aims at examining the degradability of aniline in aqueous solutions by ozone-induced cleavage, and at determining the kinetics of the cited cleavage reactions. Aniline was prepared in four different concentrations and the flow rate of ozone supplied to each solution was selected. Aniline solutions were ozonated at low and high pH, so as to compare both. molecular and hydroxyl free radical mechanisms, respectively. The main identified aromatic by-products were nitrobenzene,and azobenzene when the experiment was carried out at acidic pH. Formation of nitrobenzene, azobenzene, azoxybenzene and 2-pyridine carboxylic acid (picolinic acid) was observed when the ozonization was carried out at basic pH. All the aromatic by-products found were less toxic than the raw materials. The pseudo-first-order constants in aniline concentrations were calculated.
Keywords: INORGANIC-COMPOUNDS; ORGANIC-COMPOUNDS; AQUEOUS-SOLUTION; RATE CONSTANTS; OZONATION; WATER; DECOMPOSITION; Chemistry; Environmental Sciences & Ecology